141k views
0 votes
Ex / 1 - e2x d x solving this integral.

User Fraggjkee
by
4.8k points

1 Answer

6 votes

Answer:


I=(1)/(2)(\ln \left|e^x+1\right|)/(\ln \left|e^x-1\right|)+C

Explanation:

The given in integral problem is


\int (e^x)/(1-e^(2x))dx


\int (e^x)/(1-(e^(x))^2)dx

Substitute
e^x=t.


(d)/(dx)e^x=(d)/(dx)t


e^x=(dt)/(dx)


e^xdx=dt

After substitution we get


\int (t)/(1-t^2)dt

We know that


\int (1)/(a^2-x^2)dc=(1)/(2a)(\ln \left|x+a\right|)/(\ln \left|x-a\right|)+C

Using this formula we get


\int (1)/(1^2-t^2)du=(1)/(2(1))(\ln \left|t+1\right|)/(\ln \left|t-1\right|)+C

Substitute
t=e^x.


I=(1)/(2)(\ln \left|e^x+1\right|)/(\ln \left|e^x-1\right|)+C

Therefore, the solution of given integral is
I=(1)/(2)(\ln \left|e^x+1\right|)/(\ln \left|e^x-1\right|)+C.

User Legogo
by
5.0k points